Effect of Cultural Perspectives on the process of an Inclusive Education in Primary Schools in Dubai, United Arab Emirates - Calderon, Andrea (2013)
in the United Arab Emirates continues to be a key issue within the education system. Therefore, having concerns for the needs of special needs children requires responsibility and commitment amongst all members of the society. A society that relies on an education system to develop their maximum potential along with ensuring that special needs children have equal access to a quality inclusive education. The Ministry of Education (MOE) along with the Ministry of Social Affairs (MOSA) developed the Federal Law No. 29 in 2006, which specified the Rights of Individual with Special Needs supporting both the national and international inclusion philosophy. A philosophy that seeks to provide an excellent environment that meets their educational, social and emotional needs in regular settings within their community. Previous research established five major themes to explain the process of inclusion in the UAE. The first relates to the existence of SEN students and the type of disability that they have. Second mentions the type of teachers and professionals within inclusive settings. Third states the provision of all additional aids and technological services. Fourth expresses the accommodations done to the school´s facilities to ensure the inclusion of the children. Finally, the fifth one expresses the existing professional development conferences that allow teachers to improve their practices. Leaders and policy makers consider inclusion as an adequate educational model due to the acceptance and supports that SEN students have from their peers and other people of their school community. Previous studies have shown that SEN students were being educated within public and private schools. It is believed that a complex group of people with cultural beliefs and professional experiences affects the perception of the school community of the children with special needs. Inclusion requires a restructuring of mainstream schools to make the necessary accommodations for every student regardless of their ability or disability. Therefore, the following discussion is focused to express the effect of cultural perspectives on the process of an inclusive education in primary schools in Dubai. It aims to explain the attitudes of administrators, teachers and parents through document analysis, questionnaires and interviews. Responses were received from twelve teachers and parents along with 6 administrators from two schools one that followed the IB curriculum and one that followed the UK curriculum. It also seeks to determine the challenges, changes and current practices of inclusion within a multicultural country.